Algorithm for predicting low maintenance doses of warfarin using age and polymorphisms in genes CYP2C9 and VKORC1 in Brazilian subjects - de Oliveira Magalhães Mourão, Aline; Braga Gomes, Karina; Afonso Reis, Edna; Pedra de Souza, Renan; de Freitas Campos, Emílio Itamar; Dias Ribeiro, Daniel; da Costa Rocha, Manoel Otávio; Parreiras Martins, Maria Auxiliadora (The pharmacogenomics journal, 2020)
Warfarin exhibits a wide variation in dose requirements. We sought to evaluate the association of polymorphisms CYP2C9*2 (rs1799853), CYP2C9*3 (rs1075910), and VKORC1-G1639A (rs9923231) and nongenetic factors with maintenance doses of warfarin <17.5 mg/week and to create an algorithm to predict drug sensitivity. This is a retrospective cohort study including 312 patients assisted at an anticoagulation clinic in Brazil. The mean age of participants was 60.4 ± 13.5 years and 59.9% were female. The logistic regression model included: age [odds ratio (OR) 1.03, 95% confidence interval (CI) 1.01–1.06], genotype VKORC1 AA (OR 31.61, 95% CI 11.20–100.15) and genotype CYP2C9 2/2, 2/3 or 3/3 (OR 16.48, 95% CI 3.37–81.79). The creation of our algorithm involved warfarin-experienced patients on stable doses, identifying factors associated with drug sensitivity. The validation of this algorithm allows its use in future populations to determine the initial dose distinguishing patients with dose requirements <17.5 mg and reducing time to achieve stable doses.